‘Playing the Man’ the Courage of Christian Martyrs, Translated and Transposed - Moriarty, Rachel (Studies in church history, 1998)
The aged Bishop Polycarp was burnt to death in the arena at Smyrna in the afternoon of 23 February 155 (or 156), in front of a hostile crowd. The terrible story was lovingly recorded, copied and passed round the churches; it is probably the first non-biblical record of a martyrdom, and survives by itself and in Eusebius’ History. As Polycarp entered the arena Christian eyewitnesses heard a voice from heaven, saying in Greek, for all to understand, . The first word means ‘be strong’; the last shares a root with two other Greek words, which means courage, and which means a male person, a man. We shall consider later how Polycarp’s contemporaries understood this; centuries later, about the 1880s, an Anglican academic clergyman, Joseph Lightfoot, who was soon to be a bishop himself, translated Polycarp’s story into English. He found an apt English idiom: ‘Be strong, Polycarp,’ he wrote, ‘and play the man.’